2013
DOI: 10.1371/journal.pone.0059086
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Artemisinin Derivatives and Lipid Nanoparticle Formulations Inhibit Growth of Breast Cancer Cells In Vitro and Induce Down-Regulation of HER Family Members

Abstract: Artemisinin (ART) dimers show potent anti-proliferative activities against breast cancer cells. To facilitate their clinical development, novel pH-responsive artemisinin dimers were synthesized for liposomal nanoparticle formulations. A new ART dimer was designed to become increasingly water-soluble as pH declines. The new artemisinin dimer piperazine derivatives (ADPs) remained tightly associated with liposomal nanoparticles (NPs) at neutral pH but were efficiently released at acidic pH's that are known to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 62 publications
0
39
0
Order By: Relevance
“…48 The immortal nontumorigenic human breast epithelial cell line, MCF10A, was less susceptible to both the free compound and its liposome formulations. In both NP109 30 and NP209 assays, more than 50% of MCF10A cells were still viable after 48 h of incubation at 10 μM ADP109 concentration. We have yet to test concentrations higher than 10 μM on MCF10A cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 The immortal nontumorigenic human breast epithelial cell line, MCF10A, was less susceptible to both the free compound and its liposome formulations. In both NP109 30 and NP209 assays, more than 50% of MCF10A cells were still viable after 48 h of incubation at 10 μM ADP109 concentration. We have yet to test concentrations higher than 10 μM on MCF10A cells.…”
Section: Resultsmentioning
confidence: 99%
“…30 To evaluate pH-responsive drug release, NP209 was exposed to pH 7.4, 6.0, and 4.0 to measure the ART dimer release over time. NP209 released ADP109 more efficiently at pH 4 than physiological neutral.…”
Section: Resultsmentioning
confidence: 99%
“…Anticancer properties of pure artemisinin and its derivatives and different combination therapies with it are shown in many in vivo and in vitro experiments, [1][2][3] but there are no studies on its combination with butyric acid and miconazole. Anticancer effects of butyric acid and miconazole are suggested in a few publications.…”
Section: Introductionmentioning
confidence: 99%
“…This compound is a sesquiterpene phytolactone with an endoperoxide bridge (R-O-O-R'), which induces lipid proxidation by forming carbon-based free radicals after reacting with the iron atom. [2] Artemisinin acts selectively on malarial parasites or cancerous cells, because they have large quantities of iron deposit due to their metabolic activity. Many studies have shown that artemisinin has different cytotoxic effects on various cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Artemisinin, the primary component of ACT, is a naturally produced sesquiterpene lactone endoperoxide. Artemisinin and its derivatives have also been found to exhibit anti-cancer properties (Ferreira et al, 2010) such as inducing apoptosis in lung cancer cells (Gao et al, 2013) and preventing cell proliferation in breast cancer cells (Ba et al, 2012; Zhang et al, 2013). In nature, artemisinin is synthesized by the plant Artemisia annua through conversion of the intermediate sesquiterpene farnesyl pyrophosphate (FPP; Bertea et al, 2005; Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%